2009
DOI: 10.1080/09723757.2009.11886055
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Lactate Dehydrogenase (LDH) Isoenzyme is a Biochemical Tumour Marker in Cervical Carcinoma Patients

Abstract: To establish Lactate dehydrogenase (LDH) isoenzyme is a biochemical tumor marker in cervical carcinoma patients for diagnosis and treatment monitoring of the disease. The Serum and cervical tissue LDH isoenzyme was analyzed qualitatively by Poly Acrylamide Disc Gel Electrophoresis method. The total LDH activity was estimated quantitatively by the method of UV spectrophotometry. 50 untreated cervical carcinoma patients were taken up and compared with age matched healthy females (controls). Out of 50 patients, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…The results in Table (1) showed a significant increase (p≤ 0.05) in LDH activity in the serum of uterine cancer females compared with the healthy females. The obtained results were in agreement with those reported by other investigators (Subramanian et al, 2009;Kumar et al, 1988), which showed a higher activity of LDH in cervical cancer patients.…”
Section: Lactate Dehydrogenasesupporting
confidence: 93%
See 1 more Smart Citation
“…The results in Table (1) showed a significant increase (p≤ 0.05) in LDH activity in the serum of uterine cancer females compared with the healthy females. The obtained results were in agreement with those reported by other investigators (Subramanian et al, 2009;Kumar et al, 1988), which showed a higher activity of LDH in cervical cancer patients.…”
Section: Lactate Dehydrogenasesupporting
confidence: 93%
“…On the other hand, Subramanian et al, (2009) recorded changes in the total LDH activity in serum and tissues of cervical carcinoma patients, and they suggested that LDH isoenzyme is a useful biochemical tumor indicator for diagnosis and treatment monitoring of the disease, and to assess the grade of malignancy. The increase of LDH activity may be attributed to the genomic changes during malignant transformation, the main reason for the increase of LDH was due to increased tumor cells also produce more amount of lactic acid, and mainly due to the breakdown of glycoprotein into lactic acid formation (Subramanian et al, 2009).…”
Section: Lactate Dehydrogenasementioning
confidence: 99%
“…[17] The study conducted by Subramanian et al in 2009 on cervical carcinoma has concluded that LDH isoenzyme is an important biochemical marker in assessing the grade of malignancy. [18] In the present study, serum LDH level did correlate with the histological grade of OSCC.…”
Section: Discussionmentioning
confidence: 67%
“…Serum LDH isoenzyme levels have been studied extensively in various body cancers and increased levels have been observed. [ 15 16 17 18 19 ] Malignant tumor tissue or contiguous tissue damaged by tumor liberates enzymes into circulation, which contributes toward abnormal increase in enzyme levels. Irrespective of tissue of origin, studies on isoenzyme distribution in different types of malignant tumors have shown cathodic isoenzymes LDH 3, LDH 4 and LDH 5 to be abnormally increased.…”
Section: Discussionmentioning
confidence: 99%